Comparative transcriptome analysis of the resistance mechanism of Hemerocallis citrina Baroni to Puccinia hemerocallidis infection - Lijie Zhang; Lingling Zhou; Jiali Meng; Shaojun Wu; Shuhua Liu; Nianfu Yang; Fufa Tian; Xiang Yu (Journal of Plant Interactions, 2023)
ABSTRACTHemerocallis citrina Baroni (daylily) is an important cash crop in many regions of China. Daylily rust caused by Puccinia hemerocallidis (Ph) is a major disease in H. citrina. Rust infection on the leaves of two resistant and susceptible varieties of H. citrina was examined. Transcriptome sequencing and defense enzyme activity were used to analyze the differential expression of related genes after 0, 72, 144, 192, and 288 h, to reveal the response mechanism of H. citrina to rust infection and screen-related resistance genes. The results suggested that 72 h after Ph infection was the key time point for determining differences between resistant and susceptible varieties. DEGs were significantly enriched in phenylpropanoid biosynthesis, plant–pathogen interaction, plant hormone signal transduction, and the MAPK signaling pathway. TFs WRKY33 and CYP98A are key genes closely related to the disease-resistance response of H. citrina. This study is the first large-scale transcriptomic analysis of H. citrina.